FISHING RESOURCES ORIGINATED FROM OF THE ARTISANAL FISHING IN THE JURUMIRIM RESERVOIR, PARANAPANEMA RIVER, UPPER PARANÁ, BRAZIL - Novaes, José Luís Costa; Carvalho, Edmir Daniel [UNESP] (My University, 2009)
The aim of this paper was to evaluate the artisanal fisheries in the village of fishermen of Bairro da Ponte, Jurumirim reservoir. Data were collected using production forms which were filled daily by a data collector, in 2005 and 2006. The fishery yield was estimated at 15.7 kg ha-1 year-1, the average yield was 12.5 t year-1 and catch per unit effort (CPUE) was 10.5 kg fisherman-1 day-1. We recorded 26 species of landed fish in this activity, being the “traíra” (Hoplias malabaricus) the most landed fish in terms of biomass with 6,158.5 kg, representing 24.5%, of the total landed. Seasonally, the CPUE ranged from 14.5 kg fisherman-1 day-1 in summer/2005 to 9.0 kg fisherman-1 day-1 in spring/2006. The average CPUE by type of fish also showed a marked seasonality. In summer of 2005 and 2006, “curimbatá” was the most landed fish, with CPUE kg fisherman-1 day-1 of 6.9 and 6.2, respectively. The “piavas” were the most landed fish in autumn with CPUE of 2.4 (year 2005) and 2.3 (year 2006) kg fisherman-1 day-1, and “traíra” in winter with CPUE ranging from 3.0 to 4.0 kg fishrman-1 day-1, in 2005 and 2006, respectively. The mathematical modeling of simple linear regression indicated positive relationships between the monthly fish production and the number of boats in activity and of fishing trips. The study concluded that fishing is sustained only by native species; with marked seasonality for catching fish and that the area of fishing examined of the Jurumirim reservoir is among the most productive areas of the Upper Paraná basin.
RECURSOS PESQUEIROS ORIUNDOS DA PESCA ARTESANAL NO RESERVATÓRIO DE JURUMIRIM, RIO PARANAPANEMA, ALTO PARANÁ, BRASIL
Keywords: artisanal fisheman; curimbatá; landing fisheries; São Paulo State; Traíra